Overview of The Electric Vehicle Charging Station Business in Thailand - Charoenthongthae, Thawanya; Thanomtheeranant, Krissana (Journal for Strategy and Enterprise Competitiveness, 2023)
The starting point for being an entrepreneur is finding an idea to create a new business, having the mindset that it can be done. There is a 3-step process for creating a new business: asking questions: (1) What are you doing? (2) Are you doing it well? and (3) how to do it. Getting the answer is Research to find as much information and be as comprehensive as possible for decision making to create a new business This is the same as becoming an electric vehicle charging point business operator. This academic article aims to study and present four important content points: 1) electric cars, 2) low-carbon society, 3) measures to promote electric vehicles in Thailand, and 4) the business of electric vehicle charging points in Thailand. The electric vehicle charging point business in Thailand is one worth keeping an eye on right now. Because the number of electric cars in Thailand is increasing every year. In line with the trend of saving the world, reducing global warming, and also receiving support from the government for the purchase and production of electric cars in the country. When electric cars are used more in the future the electric vehicle charging point business will have to expand as well. This is because there are not many electric vehicle charging point businesses at present. Entrepreneurs can expand their business from their original venture without having to start from scratch. Therefore, investing in the electric vehicle charging point business is another interesting business in this decade.